Theoretical Studies on the Structure-activity Relationships for Thionocarbamates as Selective Collectors for Copper Sulfide Minerals - G. Y. Liu (International Mineral Processing Congress, 2014)
The structure-activity relationships for four thionocarbamate collectors are discussed in this pa-per. These collector classes are alkyl alkyl thionocarbamates, allyl alkyl thionocarbamates, acyl al-kyl thionocarbamates and alkoxylcarbonyl alkyl thionocarbamates. The main emphasis will be to highlight the differences between collectors and their affinities for copper and iron sulfide minerals on the basis of data on electronic-structure properties obtained by vacuum and solution density functional calculations, flotation experiments and analysis measurements. The mechanism of interaction of these collectors with sulfide minerals is also discussed with perturbation theory. The theoretical study results indicate that acyl alkyl thionocarbamates and alkoxylcarbonyl alkyl thionocarbamates have best performance in these agents as flotation collectors with improved collecting power for copper sulfide minerals and excellent selectivity against iron sulfide minerals, which are consistent with the experimental data reported in the literature.